CFD investigation of a distributed propulsion system - Chng, Jia Yang (Nanyang Technological University, 2022)
Since the advent of commercial jet transport aircraft, a lot of research has been done to improve aircraft performance. This paper analyses the effectiveness of a distributed propulsion system in increasing an aircraft’s aerodynamic efficiency. A distributed propulsion system uses a series of engines distributed span-wise across the aircraft’s wing with the aim to increase aircraft performance. Numerical simulation using computational fluid dynamics is used in this paper to determine the lift and drag forces, and subsequently the aerodynamic efficiency of a 3-D finite wing in ANSYS Fluent. The computational domain utilized an overset mesh with the component consisting of the finite wing and equally spaced momentum sources representing propellers mounted on the wing. To this end, the distributed propulsion system was found to be able to increase the lift performance and aerodynamic efficiency of a finite wing by reaping the benefits of boundary layer ingestion. Tilting the propellers at a relative angle from the wing was found to be more efficient in generating lift. Additionally, increasing the percentage throttle was also found to be able to improve lifting characteristics and efficiency of the finite wing.